Perancangan Backup Link Menggunakan Metode HSRP (Hot Standby Router Protocol) Dalam Penyediaan Layer-3 Redundansi - Geraldi, Tommy Elco; Wahyuddin, Moh. Iwan; Aningsih, Andri (STMIK Budi Darma, 2020)
With the increase of internet user today, if it only has one router, when the router experiencing a network failure, then the internet cannot be used. To overcome this problem, the HSRP (Hot Standby Router Protocol) method by creating one active link and one backup link has been applied in the previous research. In this research will be applying the HSRP, VTP (Vlan Trunking Protocol), InterVLAN, and VLAN (Virtual Local Area Network) as a comparison. The testing parameter in this research will be using packet loss and throughput. From the result of testing that has been done, it shows that by applying the HSRP method, it gives a network availability with the packet loss of only 0,32%, and throughput of 1,159Mb/s (95,58%) from using 100 PC.